Makna Pelayanan Prima dari Perspektif Karyawan Hotel: (Studi di Kinasih Resort Depok) - Johann Wahyu Hasmoro Prawiro; Ammar Harun Rizki (CV. ALIM'SPUBLISHING, 2026)
This study aims to explore the meaning of service excellence from the perspective of hotel employees at Kinasih Resort Depok, Indonesia. Most existing research on service excellence has focused on guest satisfaction, leaving the subjective experiences of employees as service providers underexplored. This study employs a qualitative approach with a descriptive phenomenological design. Data were collected through in-depth interviews, participatory observation, and documentation from five purposively selected informants across the F&B Service, Housekeeping, Front Office, Human Resources, and management departments. Data analysis followed Moustakas's phenomenological procedure encompassing epoché, horizonalization, theme clustering, and essence description. Findings reveal that employees construct layered meanings of service excellence according to their hierarchical positions: frontline workers emphasize friendliness and responsiveness, supervisors emphasize speed and problem resolution, while management frames it as a holistic service ethos encompassing internal relationships. Emotional labor emerged as an inevitable dimension managed through collaboration, prioritization, and de-escalation strategies. Organizational factors including training systems, communicative leadership, guest feedback-based evaluation, and managerial attention to employee well-being demonstrably shape how employees internalize service excellence values. This study contributes to employee-centered literature on service excellence and offers practical implications for human resource development in resort contexts.